Effect of foliar spraying with GA3 and phosphate potassium on growth and yield of potato solanum tuberosum - شيخ سليمان, نصر; عثمان, جنان; حيدر, سوزان (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out in spring loop in the village of saran in 2019, to study effect of foliar spraying with only GA3 or with phosphate potassium on growth and yield of potato solanum tuberosum cv.Binella, the study used arandomized complete block design, the study included six treatments spraying with GA3 at aconcentration of 100-50 ppm, and spraying with phosphate potassiumat aconcentration of1.5 g/l, spraying with GA3 at aconcentration of 100ppm+ spraying with phosphate potassiumat aconcentration of1.5 g/l, spraying with GA3 at aconcentration of 50 ppm+ spraying with phosphate potassiumat aconcentration of1.5 g/l, in addition to the witness that the plants were sprayed with distilled water. The results showed that the treatment of potato plants with GA3 and PK had appositive effect on the studied morphine traits and production indicators. The treatment of plant with GA3 at aconcentration of 100ppm with PK at aconcentration of 1.5g/l was significantiy outperformed all the studied treatments in terms of the area of paper survey, it reached(17384 cm2/plan), and his proof (8.278), the height of the plant (55 cm), the production of the plant with avalue of (1817 g/plant), productivity of the unit area (8.65kg/m2), the number of tuber (15.41 tuber/plant), and the average and that the tuber (118 tuber/plant).